1999
DOI: 10.1097/00002030-199910220-00009
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of isoniazid chemoprophylaxis for HIV-infected drug users at high risk for active tuberculosis

Abstract: The completion of isoniazid chemoprophylaxis was associated with a marked reduction in tuberculosis risk among tuberculin reactors and anergic persons in this high-risk population. These data support aggressive efforts to provide a complete course of preventative therapy to HIV-infected tuberculin reactors, and lend weight to the findings of others that isoniazid can reduce the rate of tuberculosis in high-risk anergic HIV-infected persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
1
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 15 publications
4
54
1
1
Order By: Relevance
“…An increase in liver enzymes has been described as a relatively frequent adverse event of INH treatment (Blumberg et al 2005), which was observed in two patients of the present study who did not have hepatitis B or C. These results mainly show mild, clinically manageable adverse events and the absence of death or any interaction that may objectively impair follow-up parameters of HAART (CD4 and viral load) and are in agreement with the literature regarding the use of INH chemoprophylaxis (Gourevictch et al 1999, de Pinho et al 2001). …”
Section: Discussionsupporting
confidence: 92%
“…An increase in liver enzymes has been described as a relatively frequent adverse event of INH treatment (Blumberg et al 2005), which was observed in two patients of the present study who did not have hepatitis B or C. These results mainly show mild, clinically manageable adverse events and the absence of death or any interaction that may objectively impair follow-up parameters of HAART (CD4 and viral load) and are in agreement with the literature regarding the use of INH chemoprophylaxis (Gourevictch et al 1999, de Pinho et al 2001). …”
Section: Discussionsupporting
confidence: 92%
“…INH completion in the routine care group was 13.1%, even lower than the 26% found among homeless clients at the same TB clinic by Tulsky et al (2000). Likewise, INH completion rates in the methadone groups were lower than in uncontrolled studies in methadone maintenance clinics that reported completion rates of 80-90% (Gourevitch et al, 1996;Gourevitch et al, 1998;Snyder et al, 1999).…”
Section: Discussioncontrasting
confidence: 55%
“…A commonly used chemoprophylaxis regimen is 6 months of isoniazid (INH), which decreases occurrence of active TB by 60-90% (Ferebee, 1970;Comstock and Woolpert, 1984; Centers for Disease Control and Prevention (CDC), 1990; Pape et al, 1993) and was at the time of this study the preventive therapy recommended by the American Thoracic Society and the Centers for Disease Control and Prevention (Bass et al, 1994). If, however, patients do not complete preventive therapy, they derive less benefit and develop TB at a higher rate (Gourevitch et al, 1998). Chemoprophylaxis completion rates are frequently low; only about half of patients complete the 6-month course (Centers for Disease Control and Prevention (CDC), 1995b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is contrary to our findings. Chemoprophylaxis in this high risk group is associated with marked reduction in tuberculosis risk [17,18]. Some authors however do not conform to this view [19].…”
Section: Discussionmentioning
confidence: 98%